Directional Solidification of Dilute Sn-Pb Alloys - Schulz-Eglin, B; Bustos-Castillo, O (MANEY PUBLISHING, 2012)
Microstructure evolution and pattern formation during directional solidification of dilute Sn-Pb system were analysed. Planar, cellular and dendritic morphologies were obtained by adequate thermal gradient and interface velocity control. The samples were obtained from pure elements in concentrations of 0.05, 1.0 and 4.0 wt-% Pb. Growth was carried out in a Bridgman device in the velocity range of 0.38-30 mu m s(-1) at thermal gradients from 1.3 to 2.6 degrees C mm(-1). The samples were examined using metallographic techniques to determine their morphology and dimensional characteristics. The system was analysed to describe the different stages of evolution of the morphology and transitions. It was observed that both primary cellular and dendritic spacing decreased with increasing velocity. However, in the cellular-dendritic transition zone, an important increase in spacing was detected and basically associated with convective effects during irregular cellular growth.